2018
DOI: 10.7150/jca.19185
|View full text |Cite
|
Sign up to set email alerts
|

GP73 level determines chemotherapeutic resistance in human hepatocellular carcinoma cells

Abstract: Objective GP73 is a new hepatocellular carcinoma (HCC) marker, which is highly expressed in hepatocellular carcinoma and closely relates to prognosis. This study was to investigate the effects of GP73 on cellular proliferation, apoptosis, oxaliplatin (OXA) resistance and secretory clusterin (sCLU) of HCC cells.Materials and Methods Western blot and immunofluorescence was used to detect the expression of GP73 in 8 types of commonly used HCC cell lines. Drug resistance was induced by increasing concentration gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…As shown in Figure 8 ( A1-A12 ), a better OS was predicted to couple with increased expression of Nrf1, CHP2 ( calcineurin like EF-hand protein 2 ), CPS1 ( carbamoyl-phosphate synthase 1 ), FOXO1 ( forkhead box O1 ), IRS4 ( insulin receptor substrate 4 ) and/or NKX2-8 ( NK2 homeobox 8 ); this was also accompanied by reduced expression of AKR1B10 ( aldo-keto reductase family 1 member B10 ), EPO ( erythropoietin ), MUTYH ( mutY DNA glycosylase ) and/or PKM ( pyruvate kinase M1 /2). Besides, GP73 (also called GOLM1, golgi membrane protein 1) has been shown as a potential diagnostic marker for primary HCC [63,64], while GPC3 (glypican 3) acts as another key biomarker for early diagnosis of human HCC and a rational immunotherapeutic target for HCC [65,66].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 8 ( A1-A12 ), a better OS was predicted to couple with increased expression of Nrf1, CHP2 ( calcineurin like EF-hand protein 2 ), CPS1 ( carbamoyl-phosphate synthase 1 ), FOXO1 ( forkhead box O1 ), IRS4 ( insulin receptor substrate 4 ) and/or NKX2-8 ( NK2 homeobox 8 ); this was also accompanied by reduced expression of AKR1B10 ( aldo-keto reductase family 1 member B10 ), EPO ( erythropoietin ), MUTYH ( mutY DNA glycosylase ) and/or PKM ( pyruvate kinase M1 /2). Besides, GP73 (also called GOLM1, golgi membrane protein 1) has been shown as a potential diagnostic marker for primary HCC [63,64], while GPC3 (glypican 3) acts as another key biomarker for early diagnosis of human HCC and a rational immunotherapeutic target for HCC [65,66].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the correlation between GP73 expression and chemotherapy response in cancer is unclear. Ye et al reported that GP73 may signi cantly change cell proliferation and apoptosis so as to in uence the oxaplatin resistance in hepatic carcinoma cells [20]. Zhou et al's study found that GP73 induced cisplatin resistance in HT29 colon cancer cells was related to the activation of the mitogenactivated protein kinase/ERK and Wnt/β-catenin signaling pathways [21].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the correlation between GP73 expression and chemotherapy response in cancer remains to be determined. Ye et al reported that GP73 affect the oxaplatin resistance by involving in the cell proliferation and apoptosis process in HCC [20]. Zhou et al's study found that GP73 induced cisplatin resistance in HT29 colon cancer cells was related to the activation of the mitogen-activated protein kinase/ERK and Wnt/β-catenin signaling pathways [21].…”
Section: Discussionmentioning
confidence: 99%